Depression and anxiety among HIV-positive men who have sex with men and men who have sex with women in China. Issue 3 (3rd March 2020) - Aunon, Frances M.; Simoni, Jane M.; Yang, Joyce P.; Shiu, Chengshi; Chen, Wei-Ti; Edmunds, Sarah R.; Ramaiya, Megan; Cheng, Joy; Zhao, Hongxing
ABSTRACT: China is experiencing an emerging HIV epidemic among men who have sex with men (MSM). Minority stress theory posits that marginalized populations experience additional stress, which influences experiences of psychological distress and health outcomes. This study aimed to understand psychological distress of MSM relative to men who have sex with women (MSW) in an urban Chinese setting. Cross-sectional survey data were collected from 162 HIV-positive Chinese men receiving HIV treatment at Beijing's Ditan Hospital. Multiple linear regression with imputation was used to identify correlates of psychological distress. Relative to MSW, MSM were younger, more educated, and less likely to be in a relationship or have children. While both groups reported clinically elevated levels of depression and anxiety, sexual behavior was not associated with either outcome. Higher endorsement of depression symptomology was associated with worse reported physical health ( β  = −1.37, p  < .05) and greater endorsement of maladaptive coping ( β  = 2.39, p  < .05), whereas higher endorsement of anxiety symptomology was associated with greater endorsement of adaptive coping ( β  = 0.78, p  < .05), diminished physical health ( β  = −0.86, p  < .05), and a high school or greater level of education ( β  = 4.13, p  < .05). These findings suggest that interventions targeting coping strategies may address psychological distress among HIV-positive Chinese men.